2021
DOI: 10.3324/haematol.2019.233056
|View full text |Cite
|
Sign up to set email alerts
|

The Hsp70 chaperone system: distinct roles in erythrocyte formation and maintenance

Abstract: Erythropoiesis is a tightly regulated cell differentiation process in which specialized oxygen- and carbon dioxide-carrying red blood cells are generated in vertebrates. Extensive reorganization and depletion of the erythroblast proteome leading to the deterioration of general cellular protein quality control pathways and rapid hemoglobin biogenesis rates could generate misfolded/aggregated proteins and trigger proteotoxic stresses during erythropoiesis. Such cytotoxic conditions could prevent proper cell diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 150 publications
1
16
0
Order By: Relevance
“…Our analytical and bioinformatic structural data presented refer exclusively to the human, K562 pro‐erythroid, hemin‐responsive cells. Among the HeBPs identified in this study, GAPDH (Chakravarti et al, 2010; Dai et al, 2020; Sweeny et al, 2018), the heterogeneous ribonucleoprotein A2/B1 and HSP70 (Famin & Ginsburg, 2003; Li et al, 2003; Mathangasinghe et al, 2021; Rio et al, 2019) have been established in the literature as heme associated species, therefore strengthening the validity of our findings. Furthermore, the String bioinformatic analysis shown in Figure 5 (https://string-db.org/) revealed strong associations among the majority of the 45 HeBPs.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our analytical and bioinformatic structural data presented refer exclusively to the human, K562 pro‐erythroid, hemin‐responsive cells. Among the HeBPs identified in this study, GAPDH (Chakravarti et al, 2010; Dai et al, 2020; Sweeny et al, 2018), the heterogeneous ribonucleoprotein A2/B1 and HSP70 (Famin & Ginsburg, 2003; Li et al, 2003; Mathangasinghe et al, 2021; Rio et al, 2019) have been established in the literature as heme associated species, therefore strengthening the validity of our findings. Furthermore, the String bioinformatic analysis shown in Figure 5 (https://string-db.org/) revealed strong associations among the majority of the 45 HeBPs.…”
Section: Discussionsupporting
confidence: 81%
“…Our analytical and bioinformatic structural data presented refer exclusively to the human, K562 pro-erythroid, hemin-responsive cells. Among the HeBPs identified in this study, GAPDH (Chakravarti et al, 2010;Dai et al, 2020;Sweeny et al, 2018), the heterogeneous ribonucleoprotein A2/B1 and HSP70 (Famin & Ginsburg, 2003;Li et al, 2003;Mathangasinghe et al, 2021;Rio et al, 2019) In conclusion, the sum of findings presented above, provide evidence that human pro-erythroid K562 cells contain a large number of different classes of HeBPs with distinct heme-binding motifs (HBMs) that contribute to the diverse pleiotropic roles of heme as a key regulator of cellular homeostasis (Roumenina et al, 2016). We anticipate that this new set of findings can expand further studies on F I G U R E 6 Illustration of the 45 heme-binding proteins (HeBPs) identified in human K562 cells by HACC, LC-MS/MS proteomic profiling, and HEMOQUEST analysis.…”
Section: Discussionmentioning
confidence: 77%
“…Such a shift, evident from the first 12 h in some cases, is indicative of the need to keep up with proteostatic and redox imbalances as well as of an array of insults to the RBC integrity. On the one hand the HSP70 system, that accounts for ∼1/3 of the RBCs’ chaperome and is responsible for prevention of protein aggregation, protein disaggregation and protein refolding ( Mathangasinghe et al, 2021 ), translocates to protect membrane proteins. Accordingly, the antioxidant peroxiredoxin-2 when bound to the membrane seems to ameliorate the detrimental effects of oxidized Hb ( Cha et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Once the terminal erythroblasts enter the rapid cell cycle, one of the major consequences of the fast turnover of erythroid proteome is the accumulation of misfolded or aggregated proteins that could be deleterious to differentiation. Therefore, erythroblasts in the final stages of terminal differentiation establish a quality control system involving heat shock protein 70 (Hsp70) chaperon system to maintain the proper functions of erythroid specific proteins [24]. The posttranslational regulation of proteome in the final stages of terminal erythropoiesis also involves microRNAs [25].…”
Section: Proteome Remodeling: Tuned From Transcription To Epigenetic ...mentioning
confidence: 99%